Financial Development and Investment in Emerging Economies: The Role of Macroeconomic and Institutional Conditions - Alsubaie, Ali (International Journal of Economics and Financial Issues, 2026)
This study examines the relationship between financial development and capital investment in emerging economies, with particular attention to macroeconomic conditions and institutional quality as transmission factors. Using panel data for 30 emerging economies from 2002–2021, the analysis employs fixed-effects estimation with clustered standard errors and alternative institutional indicators to assess the robustness of the finance–investment nexus. The results indicate that financial development has a strong, statistically significant positive effect on capital investment (a one-standard-deviation increase in financial development is associated with about a 2 percentage-point rise in investment-to-GDP). Macroeconomic conditions also influence investment dynamics: economic growth is positively associated with investment, whereas external debt exerts a consistently negative effect, suggesting that debt burdens may constrain capital formation. In contrast, institutional quality does not significantly modify the financial development–investment relationship. These findings suggest that financial deepening promotes capital investment largely independently of cross-country institutional variation, although macroeconomic stability remains important for sustaining investment capacity.